Analisis Relasi Kekuasaan dan Kesenjangan Kewenangan antar Stakeholder dalam Pengelolaan Sampah di TPA Cipeucang Kota Tangerang Selatan - Luthfia Shabira; TB. Yudi Muhtadi; Eko Prasetyo (Policy, Law and Political Research Center, 2026)
This study examines stakeholder dynamics in waste management at the Cipeucang Landfill and analyzes how institutional roles, interests, and authority structures shape policy implementation. The research was conducted from January to April 2025 at the landfill site and the South Tangerang City Environmental Agency. Using a descriptive qualitative approach, data were collected through in-depth interviews with officials from the Environmental Agency (DLH), managers of the Technical Implementation Unit (UPT), landfill workers, and community representatives, supported by observation and document analysis. The findings reveal that the waste management crisis stems primarily from relational and institutional fragmentation rather than purely technical limitations. First, a structural disconnection exists between the Environmental Agency as the dominant policy-making authority and the UPT as the operational implementer with limited decision-making power. Second, coordination gaps constrain resource allocation, particularly land expansion and budget optimization. Third, operational innovations such as maggot cultivation demonstrate technical feasibility but remain institutionally marginalized due to weak cross-level integration. The study recommends strengthening coordination mechanisms, clarifying institutional authority, and expanding public participation to foster a more integrated, participatory, and sustainable waste management system.